+0  
 
0
75
3
avatar+2346 

Let  \(f(x) = Ax - 2B^2\)and \(g(x) = Bx\), where \(B \neq 0\) . If \(f(g(1)) = 0\) , what is \(A\)  in terms of \(B\)?

tertre  Feb 5, 2018
Sort: 

3+0 Answers

 #1
avatar+85757 
+2

f(x)  =   Ax - 2B^2      g(x)   =  Bx      

 

g(1)  =  B(1)  = B

 

So

 

f( g(1) )  =  f(B)   =  0

 

A(B) -  2B^2  =  0

 

A (B)  =  2B^2       

 

A  =    2B

 

 

cool cool cool

CPhill  Feb 5, 2018
 #2
avatar+2346 
+1

Very good! Amazing, CPhill!

tertre  Feb 5, 2018
 #3
avatar+85757 
0

It was nothing....really    !!!

 

 

cool cool cool

CPhill  Feb 5, 2018

29 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details